The Effect of Menstrual Cycle on Perceptual Responses in Athletes: A Systematic Review With Meta-Analysis - Paludo, Ana Carolina; Paravlic, Armin; Dvořáková, Kristýna; Gimunová, Marta (Frontiers in Psychology, 2022)
This article aimed to investigate the effects of menstrual cycle phases on perceptual responses in athletes by means of systematic review and meta-analysis. The search was conducted in the PubMed, Web of Science, and Sport Discus databases considering articles with two or more menstrual phases for comparison. The PECO criteria were used for the keywords “menstrual cycle”, “athletes” and “perceptual responses” with their respective entry terms. Of 1.165 records identified, 14 articles were available for the final evaluation, while eight articles were eligible for a meta-analysis. The perceptual responses evaluated in the studies were: motivation, competitiveness, sleep quality, stress, muscle soreness, fatigue, perceived effort, mood, menstrual symptoms, perceived endurance, and readiness. The meta-analysis was conducted for perceived effort only. The results showed that the level of perceived exertion does not differ two phases of the menstrual cycle (MD = 3.03, Q = 1.58, df = 1, p = 0.209), whereas RPE was 19.81 ± 0.05 and 16.27 ± 0.53 at day 1-5 and day 19-24, respectively. Two studies found statistically significant changes in motivation and competitiveness during the cycle, with better outcomes in ovulatory than follicular and luteal. One study found an increase in mood disturbance in the pre-menstrual phase (versus mid-cycle); one decreased vigor in the menstrual phase (versus luteal); one increased the menstrual symptoms in the follicular phase (versus ovulation), and one study reported increased fatigue and decreased sleep quality on luteal phase (versus follicular). The remaining studies and variables were not affected by the menstrual cycle phase. Based on the results from the studies selected, some perceptual responses are affected in different menstrual cycle phases. A “favorable” subjective response in athletes was noticed when the ovarian hormones present an increase on concentration levels compared to phases with lower concentration. Different perceptual variables and methodological approaches limit the generalization of the conclusion.